Taṭwīr al-māddah al-dirāsiyyah lil-khaṭṭ al-qāʾimah ʿalā ṭarīqah al-kitābah al-iʿtiyādiyyah fī qism taʿlīm al-lughah al-ʿArabiyyah bi-Jāmiʿah Hāshim Ashʿarī Jombang - Ichyaâ€™u Hammamiz Zaman; Abdul Qodir (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2022)
This research has been conducted in the Study Program of Arabic Language Education at the University of Hasyim Asy'ari Jombang, researchers see the phenomenon of various problems. One of them in the process of teaching and learning Arabic (Khat) many of the students and lecturers do not use effective learning methods. Research methodology using quantitative and qualitative methods. While the research method used is research and development (R&D) by using the development model (ADDIE) by using the model pnengembangan researchers can produce a product that is Khat teaching materials using the method kitabah I'tiyadiah at-Tahji'iyyah. As for the research results (1) survey results after students use this product, researchers found an average score of 86.5% because the criteria table for the survey results, these results show that the product developed very well. And this is proven to help students understand the lesson (Khat) (2) the effectiveness of the development of teaching materials (Khat) based on field experiments that were tried on 15 students in the Arabic Language Education Study Program of Hasyim Asy'ari Jombang University, and with reference to the standard questionnaire results, this study received excellent scores.